Age and CD20 Expression Are Significant Prognostic Factors in Human Herpes Virus-8-negative Effusion-based Lymphoma. (December 2018) - Kubota, Tomomi; Sasaki, Yosuke; Shiozawa, Eisuke; Takimoto, Masafumi; Hishima, Tsunekazu; Chong, Ja-Mun
Abstract : Human herpes virus-8 (HHV-8)-negative effusion-based lymphoma (HHV-8-negative EBL) can be distinguished from primary effusion lymphoma based on clinical and pathologic findings. Although the morphology between the 2 is similar and they both originate from body cavities with serous effusions and are characterized by lack of tumor masses, HHV-8-negative EBL generally occurs in older patients, and has favorable response to therapy and better prognosis than primary effusion lymphoma. However, no systematic studies have investigated prognostic factors in patients with HHV-8-negative EBL. In this report, clinical and pathologic characteristics of 67 cases of HHV-8-negative EBL, including 2 of our own cases, were analyzed. Univariate analyses revealed older age (70 y and above), Japanese ethnicity, pericardial effusion, CD20 expression, and chemotherapy with rituximab were significantly favorable prognostic factors. Peritoneal effusion was identified as an unfavorable prognostic factor. In the multivariate analysis, age and CD20 expression were independent prognostic factors ( P =0.013 and 0.003, respectively). A past history of induced fluid overload, hepatitis C viral infection, and peritoneal effusion were significantly correlated with patients aged below 70 years, while pericardial and pleural effusions were significantly correlated with patients aged 70 years and above. A comparison of cases with and without CD20 expression revealed that Japanese ethnicity and pericardial effusion were significantly correlated with CD20 expression, whereas a past history of induced fluid overload and peritoneal effusion were significantly correlated with the absence of CD20. We concluded that older age and CD20 expression are significant and favorable independent prognostic factors of HHV-8-negative EBL. Abstract : Supplemental Digital Content is available in the text.